2020
DOI: 10.1055/s-0040-1714701
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Recessive Polycystic Kidney Disease—The Clinical Aspects and Diagnostic Challenges

Abstract: Autosomal recessive polycystic kidney disease (ARPKD) is one of the most common ciliopathies with kidney (nephromegaly, hypertension, renal dysfunction) and liver involvement (congenital hepatic fibrosis, dilated bile ducts). Clinical features also include growth failure and neurocognitive impairment. Plurality of clinical aspects requires multidisciplinary approach to treatment and care of patients. Until recently, diagnosis was based on clinical criteria. Results of genetic testing show the molecular basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…These clinical trials are expected to provide data on the safety, tolerability, and efficacy of tolvaptan treatment and determinants of progression in ARPKD. The genetic data collected may improve the ability to diagnose and predict the course of ARPKD, which are challenging given the genetic complexity of the disease [ 5 , 12 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These clinical trials are expected to provide data on the safety, tolerability, and efficacy of tolvaptan treatment and determinants of progression in ARPKD. The genetic data collected may improve the ability to diagnose and predict the course of ARPKD, which are challenging given the genetic complexity of the disease [ 5 , 12 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feeding difficulties may arise from compression of the stomach by enlarged organs or from the effects of kidney function impairment on appetite and/or gastric motility. Inadequate nutrition, in conjunction with risk factors such as prematurity, low birth weight, repeated hospitalization, early onset CKF, chronic hypertension, and lung disease, increase the likelihood for impaired growth and neurocognitive deficits [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a clinical case was described in six kittens that died at seven weeks of age, in which the necropsy revealed the presence of renal and bile duct cysts, undiagnosed by the young age of the animals [30]. Recent studies in human medicine reveal high genetic and clinical heterogeneity of this disease [31]. Thus, although now only the PKD1 gene has been identified as the cause of the disease in cats, several studies found cases of animals with kidney cysts and a wild-type genotype of the PKD1 gene.…”
Section: Genetic Aspects Of Feline Pkdmentioning
confidence: 99%